Electronic customer relationship management framework for Game Parks in Zimbabwe - Tsokota, Theo; Mahlangu, Gilbert; Muruko, Muchaneta Enipha; Kangara- Chipfumbu, Colletor Tendeukai (Routledge, 2022)
Electronic customer relationship management (e-CRM) is acknowledged today as an obligatory concept of customer relationship management in the world of services. However, there is a lack of any clear e-CRM framework for Game Parks in Zimbabwe. Consequently, this study’s primary objective is to address a gap existing in research to gain an appreciation of the underlying reasons affecting the adoption of available e-CRM technologies and uncover prevalent trends in Game Parks in Zimbabwe. Accordingly, the study deployed a qualitative research case study design used within a design science research framework. Thematic analysis was used to analyze data. Findings show that the studied Game Parks still use peripheral e-CRM tools at the pre-, during and post-visit stages. This was mainly due to the following; lack of financial resources, lack of employee buy-in, management domination by individuals without full knowledge of electronic tools, and customer ignorance. Consequently, results were synthesized into a framework that two experts evaluated. This study is crucial as it provides new insights on how e-CRM can be implemented for Game Parks, especially in Zimbabwe. The study augments knowledge in the field of e-CRM for Game Parks, especially in developing countries like Zimbabwe.